Design and Implementation of a Pick and Place System Using a 4 DOF Robotic Arm Integrated into a Longitudinal Horizontal Movement Base (LACCEI, 2024)
The demand of the industry has motivated articulated robotic arms to increase their work area, thus generating the need to add a greater amount of longitudinal movements in the robots, giving them an additional degree of freedom. The project consists of providing a form of integrated longitudinal movement of the translational displacement type to a 4DOF robotic arm. The project consists of providing a form of integrated longitudinal movement of the translational displacement type to a 4DOF robotic arm. This translational movement will be generated by a stepper motor connected through an endless screw with which the translational base will slide where the robotic arm will be attached. The purpose of the system is to have a cyclical pick and place sequence. To validate the design, simulations of efforts present in each component and the torque necessary to move them, in the maximum state of reach of the robot, were carried out, obtaining the most critical points of torsion moments and forces generated in the base and the screws. robot clamping. The equations that govern the positioning of the entire system were calculated, the numerical values of these equations were implemented in a Matlab code, which sends the signals to the Arduino to control the movement of the servomotors. The program implemented in Matlab allows to program the autonomous and repetitive movement by fixed and variant coordinates for specific movement points, as well as object positioning routines to key points already selected in control.